Alternative methods for angular stain control in mangoes (Mangifera indica L.) (Research, Society and Development, 2021)
The conventional methods used for angular stain control are generally chemical methods, however the use of these products can cause high environmental impact and damage to consumer health if it is used in large quantities and undiluted and applied correctly. Based on this problem, this work aimed to evaluate in vitro alternative forms of control using Saccharomyces yeast (with probiotic potential), ethanolic extracts of Mauritia flexuosa (Buriti) and Miconia albicans (Cinnamon-old) plants. To evaluate four GRAS substances in angular leaf spot control caused by Xanthomonas campestris pv. Mangifera indica, during the postharvest period in mangoes. In vitro results using antagonist yeasts showed no inhibitory effect against X. campestris. However, the extracts of the plants Miconia albicans and Mauritia flexuosa showed a significant inhibition. Thus, as two GRAS substances, 1%, 1.5% and 3% sodium carbonate and 3% sodium bicarbonate inhibited X. campestris growth 100%. Given the results obtained, the plant extracts and the GRAS substances tested were effective in controlling phytobacteria and proved to be an alternative in controlling angular leaf spot, thus avoiding economic losses during the mango postharvest phase.